Atlantic circulations - Holberton, Edward, author. Link
1 online resource (253 pages)
Keywords: "Atlantic Circulations investigates literary conversations about empire in the British Atlantic world, c.1650-1750. Reading texts by Anne Bradstreet, John Milton, Daniel Defoe, Benjamin Franklin, as well as writing by overlooked authors who deserve more attention, such as the Quaker anti-slavery activist Benjamin Lay, and the Black classicist Francis Williams, it asks how literary culture interacted with transatlantic debates about law, enslavement, economics and religious freedom. This study explores the relationship between literature and empire by joining up disciplinary areas - Early Modern English Literature and Early American Literature - which are often considered apart. It develops insights and analytical frameworks from recent British and 'Atlantic World' history to argue that the transatlantic reception of literary texts was often shaped by 'archipelagic' dynamics: political and religious tensions between and within England and Wales, and Scotland and Ireland. Atlantic Circulations examines several previously-unknown manuscripts and archives which throw new light on the circulation of literary texts in colonial culture, and reconstructs key Anglophone transatlantic cultural debates during a crucial phase of European expansion in the Atlantic world. This book will appeal to advanced students and academic researchers of early modern and eighteenth-century English literature and British cultural history, especially readers with an interest in literature's relationships with empire, colonialism and travel, and scholars of early American literature and history"--